Effects of structural modification of (alkyldiene-imidazolium bromide)-based gemini monomers on the formation of the lyotropic bicontinuous cubic phase. Issue 41 (12th October 2021) - Li, Patrick; Reinhardt, Maria I.; Dyer, Samantha S.; Moore, Kara E.; Imran, Omar Q.; Gin, Douglas L.
Abstract : Seven homologues of an amphiphilic gemini monomer were synthesized; and four of them (highlighted in red in the table) were found to form a bicontinuous cubic (Q) phase with glycerol or water and could be radically cross-linked with phase retention. Abstract : Seven homologues of an amphiphilic gemini monomer were synthesized and screened for the ability to form a bicontinuous cubic (Q) lyotropic liquid crystal phase. Four of these homologues form a Q phase with glycerol or water that can be cross-linked with retention of the nanoporous structure, with one exhibiting a well-ordered Q phase with a wider phase window than the parent monomer.